"Non-stop ecstatic dancing": An ethnographic study of connectedness and the rave experience in central Canada - Olaveson, Tim (University of Ottawa (Canada), 2004)
In this thesis I examine the rave experience in central Canada. More specifically, I investigate in detail the experience that rave's around the world have called connectedness. I begin by describing the historical antecedents to rave, which trace back much farther than most people believe. Moving through acid rock, disco, the Northern soul scene, New York garage, Chicago house, and Detroit techno, I then describe acid house---rave's immediate predecessor---and its technological quantum leaps, electronic and chemical. Discussing its roots on the island of Ibiza and in the popular culture capital of the world, "Madchester," I then trace acid house's explosion into what we now know as rave (despite the fact that the term was passe before the phenomenon had even hit North America). I then review the literature on rave culture, which falls into two broad categories: sociology and cultural studies. Finding most of these analyses lacking due to their underlying epistemological foundations and resultant methodological approaches, I illustrate how the most fruitful approach to studying rave, especially the rave experience, is an experiential one. After outlining the fundamental tenets and some methodological requirements of experiential anthropology, I describe the methods used in this research. In the following chapter, I provide a multi-sited narrative of the people and places I encountered during field research, with a particular focus on my own lived experience. I then illustrate how some aspects of rave in central Canada allow it to be characterized as a religious or spiritual experience for some participants. I go on to explore the central theme of that experience next---connectedness. Again using my own and my informants' experiences as illustrative, I outline the five key features of connectedness, in the process demonstrating its equivalence with Emile Durkheim's collective effervescence and Victor Turner's communitas. Finally, in the conclusion I pose the questions: What is the teleology of rave? and What is the future of rave? I answer these by returning to Durkheim and Turner, particularly the similar but seldom recognized processual and dialectical understanding of social life inherent in both of their anthropologies.
Keywords: Anthropology, Cultural.